What we know about emotional intelligence how it affects learning, work, relationships, and our mental health - Zeidner, Moshe; Matthews, Gerald 1957-; Roberts, Richard D. 1962- (MIT Press, 2009)
Emotional intelligence (or E.I.) is the ability to perceive, regulate, and communicate emotions, to understand emotions in ourselves and others. It has been the subject of best-selling books, magazine cover stories, and countless media mentions. It has been touted as a solution for problems ranging from relationship issues to the inadequacies of local schools. But the media hype has far outpaced the scientific research on emotional intelligence. In this book about emotional intelligence, three experts who are actively involved in research into E.I. offer a state of the art account of E.I. in theory and practice. They tell us what we know about E.I. based not on anecdote or wishful thinking but on science. E.I. promises a new means for achieving success and personal happiness. Coaches and consultants offer E.I. training and administer E.Q. tests, despite the lack of any agreement on how to measure E.I., the usefulness of testing for E.I., and even how to define E.I. This book looks at current knowledge about E.I. with the goal of translating it into practical recommendations in work, school, social, and psychological contexts. The authors discuss what is (and what isn't) E.I., why the concept has such appeal today, how E.I. develops, and the usefulness of E.I. in the real world, in school curricula, the workplace, and treating psychological dysfunction.
Keywords: Emotional intelligence; Gefühl; Emotionales Verhalten; Intelligenz